Associations between physical activity motives and trends in moderate-to-Vigorous physical activity among adolescents over five years. Issue 19 (2nd October 2021) - Abi Nader, Patrick; Gaudet, Jeffrey; Brunet, Jennifer; Gunnell, Katie E.; Doré, Isabelle; Sabiston, Catherine M.; Boudreau, Jonathan; Bélanger, Mathieu
ABSTRACT: This study examined the longitudinal associations between five physical activity (PA) motives and moderate-to-vigorous PA (MVPA) across a 5-year period spanning late childhood to middle adolescence. METHODS : Data ( n = 937; 55% girls; mean age = 10.33 years) were drawn from the Monitoring Activities for Teenagers to Comprehend their Habits study. PA motives and MVPA were assessed 15 times over the course of 5 years. Measurement invariance for the Motives for Physical Activity Measure-Revised (MPAM-R) questionnaire was established, and sex-stratified mixed-effects regression models were analysed. MVPA increased until a mean age of 12.18 years for girls and 12.89 years for boys before decreasing through the final assessment. From late childhood to middle adolescence, for boys, enjoyment motives were positively (β(95% CI) = 6.14(3.86–8.43)), while fitness motives were negatively (β(95% CI) = −4.80(−8.0, −1.59)) associated with MVPA. Whereas, for girls, competence motives were positively β(95% CI) = 3.44(1.59–5.28)) associated with MVPA Boys may benefit from PA interventions, if these were primarily aimed at increasing ones' enjoyment, whereas developing a girl's competence may provide greater contributions to a girl's future PA behaviours. PA interventions should avoid promoting the desire to be active to improve fitness, particularly among boys.